The Just In Time Teaching: The Effect on Student Learning Achievements Viewed from Learning Motivation - Alvina Barikhlana; Sholikhan Sholikhan; Hena Dian Ayu; Akhmad Jufriadi (Berkala Ilmiah Pendidikan Fisika, 2019)
The purpose of this study is to determine the effect of Just In Time Teaching using schoology and learning motivation on students learning achievement. This research was conducted in Malang Middle School. The type of research is quantitative with quasi-experimental research design. The population of this study is VIII grade students; the sample of this study is class C and D each number bout 32 students. The sample was selected using a purposive sampling technique. Data collection techniques are collected by learning achievement tests and learning motivation observation sheets. Data analysis used by two-way ANOVA analysis. The results of the study indicate that; 1) There are differences in Physics learning achievement between students who learn in using the Schoology-based on Just In Time Teaching and students who learn in using conventional learning, 2) There are differences in Physics learning achievement between students who have high learning motivation and motivated students low learning, 3) There is no interaction effect using school-based on Just In Time Teaching with learning motivation towards learning achievement. It can be concluded that Just in Time Teaching can be one solution to increase student learning achievement. Students who learn with the Schoology-based on Just In Time Teaching and students who have high motivation can improve students learning achievement.